Neuropsychological study of temperament and its relationship with relationship with associated attention disorders in 7- and 8-year-old children - Llaja Rojas, Victoria Hermila (2015)
The aim of the present investigation is to identify the mechanisms of deformation of the affective - emotive system and his relation with the disorders of attention in children between the ages from 6 to 7 years of age, the instruments used were SNT designed by Sarria 2010 and Faces Test: Yale, 2006, and the protocol of evaluation of control of the healthy child registered by the specialists pediatricians of HNERM at different stages of the children. The method used was descriptive correlational of the affective - emotive system and his relation with the disorders of attention. He arrived at the following conclusions: 1.The mother child interaction in the first stage of life has significant influence on the formation of emotional affective system and this determined a posteriori indices of attention deficit. 2. There is a direct correlation between positive emotional development and optimal level of selective attention. 3. There is a direct correlation between unfavorable emotional development and deficient level of selective attention.